IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING PROCEDURE TEXT THROUGH PICTURE WORD INDUCTIVE MODEL - Damanik, Werdi Rolando; Ownie, Sri Juriati (Universitas Negeri Medan, 2013)
ABSTRACTThis research concerned on Improving Students™ Achievement in Writing Procedure Text through Picture Word Inductive Model. In this research, the writer conducted classroom action research. Subject of this research were the second year students of SMA N 1 Pematangsiantar Class X-1 consisted of 30 students. This research was conducted in two cycles. Each cycle was organized in four steps, namely Planning, Acting, Observing, and Reflecting. Cycle II was the improvement of Cycle I. There are two kinds of data collected during the research, qualitative and quantitative data. The instruments for the quantitative data were writing test while the qualitative data was gathered through Observation Sheet, Interview Sheet and Diary Notes. Findings showed that the students™ score improve from orientation Test to Test. Based on the data analysis, Students™ mean in Test 1 was 52.40, in test II was 67.13 and Test III was 81.16. The conclusion is that Picture Word Inductive Model can improve the students™ achievement in writing procedure textKeywords: Picture Word Inductive Model, Writing, ProcedureINTRODUCTION